Longer sleep duration during infancy and toddlerhood predicts weight normalization among high birth weight infants. Issue 2 (9th November 2018) - Goetz, Amy R; Beebe, Dean W; Peugh, James L; Mara, Constance A; Lanphear, Bruce P; Braun, Joseph M; Yolton, Kimberly; Stark, Lori J
Abstract: Study Objectives: High birth weight (HBW; ≥ 4000 g) is strongly associated with later overweight, yet little is known about how to disrupt this trajectory. The current study examined sleep practices during infancy and toddlerhood among children born HBW or normal birth weight (NBW; 2500–3999 g). Methods: Latent growth curve models were used to examine sleep during infancy and toddlerhood among 270 mother–child dyads enrolled in the Health Outcomes and Measures of the Environment Study. Total sleep duration in 24 hr, sleep maintenance, and restlessness/vocalizations were collected at 6 month intervals between ages 6 and 24 months. Height and weight were obtained at ages 24 or 36 months, and normal and overweight BMI were derived. Sleep was examined among children with a normal BMI during the preschool years who were either HBW (HBW-Normal, n = 36) or NBW (NBW-Normal, n = 184) compared with overweight preschoolers (Overweight, n = 50). It was predicted that the Overweight group would have poorer sleep across infancy and toddlerhood compared with HBW-Normal and NBW-Normal. Results: HBW-Normal had the longest and Overweight had the shortest mean 24 hr sleep duration across all time points with NBW-Normal falling in-between the two groups. Compared with Overweight, HBW-Normal exhibited longer 24 hr sleep duration at age 6 months with this group difference maintained over infancy and toddlerhood. No group difference was found for NBW-Normal. Conclusions: A longer sleep duration in the first several years of life is associated with development of normal BMI among HBW children. These findings suggest that longer sleep duration may protect HBW children from becoming overweight.